Insider trading and the long-run performance of new security issues - Kahle, Kathleen M (Journal of Corporate Finance, 2000)
This paper uses insider trading around new security issues to provide evidence of managerial timing ability. I show that insider sales increase and purchases decrease prior to issues of information-sensitive securities (convertible debt and equity) by industrial firms. I then examine the relation between insider trading and subsequent stock returns. Although not all equity issues are motivated by overvaluation, those where managers sell prior to the issue are more likely to be. I find that industrial firms with abnormal insider selling underperform in the long run, whereas those with abnormal buying do not. There is no evidence of a relation between abnormal selling and future performance for utility offerings, however. Overall, the evidence is consistent with poor long-term performance being due to overvaluation.